TELORCHIS SPP. (DIGENEA: TELORCHIIDAE) IN TRACHEMYS DORBIGNI (DUMÉRIL & BIBRON, 1835) (TESTUDINES: EMYDIDAE) IN SOUTHERN BRAZIL - Mascarenhas, Carolina S. (2013)
Trachemys dorbigni, the Brazilian slider turtle, is native to Uruguay, Argentina and Brazil. In Brazil the species is abundant in the southern region. This research investigated the helminth fauna of this species. We examined sixty chelonians from aquatic environments of urban and rural areas in two municipalities in the State of Rio Grande do Sul, Brazil. During the research we found Telorchis achavali and Telorchis corti (Digenea). This is the first record of T. achavali in Brazil.